2022
DOI: 10.3390/nu14214548
|View full text |Cite
|
Sign up to set email alerts
|

Supercritical Extract of Cannabis sativa Inhibits Lung Metastasis in Colorectal Cancer Cells by Increasing AMPK and MAPKs-Mediated Apoptosis and Cell Cycle Arrest

Abstract: Colorectal cancer (CRC) is one of the diseases with the highest rates of prevalence and mortality despite therapeutic methods in the world. In particular, there are not enough methods to treat metastasis of CRC cells to distant organs. Cannabis sativa Linne (C. sativa) is a popular medicinal plant used by humans to treat many diseases. Recently, extracts of C. sativa have shown diverse pharmacological effects as a result of choosing different extraction methods. In this study, we performed experiments to confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
(33 reference statements)
0
0
0
Order By: Relevance
“…The anti-inflammatory potential of CBD has already been confirmed in several models of colitis [17]. However, a study carried out by Nallathambi et al [59] revealed that treatment with purified CBD, at different concentrations (16-252 µg/mL), resulted in a significant decrease in IL-8 levels at lower concentrations of CBD, while no anti-G0/G1 phase arrest, apoptosis (4 µg/mL), cleaved caspase-3 and PARP [88] EtOH extract totic mechanisms in colorectal cancer. , increase; , decrease; 4; CHOP, C/EBP homologous protein; eIF2α, phosphorylated P, poly (ADP-ribose) polymerase; PI3K/Akt, phosphoinositide tive oxygen species; TRPV1, transient receptor potential cation he figure was partly generated using Servier Medical Art, a Creative Commons A ribution 3.0 unported license.…”
Section: Effects Of Cannabis Sativa Extracts On Crcmentioning
confidence: 96%
“…The anti-inflammatory potential of CBD has already been confirmed in several models of colitis [17]. However, a study carried out by Nallathambi et al [59] revealed that treatment with purified CBD, at different concentrations (16-252 µg/mL), resulted in a significant decrease in IL-8 levels at lower concentrations of CBD, while no anti-G0/G1 phase arrest, apoptosis (4 µg/mL), cleaved caspase-3 and PARP [88] EtOH extract totic mechanisms in colorectal cancer. , increase; , decrease; 4; CHOP, C/EBP homologous protein; eIF2α, phosphorylated P, poly (ADP-ribose) polymerase; PI3K/Akt, phosphoinositide tive oxygen species; TRPV1, transient receptor potential cation he figure was partly generated using Servier Medical Art, a Creative Commons A ribution 3.0 unported license.…”
Section: Effects Of Cannabis Sativa Extracts On Crcmentioning
confidence: 96%